Clinical experience with Affinity Pixie™ oxygenation system in paediatric and infant patients. (May 2014) - Issitt, R; Robertson, A; Cross, N; Crook, R; Molyneux, V; Shaw, M; Walton, N; Tsang, V
Introduction: Great Ormond Street Children's Hospital undertakes over 500 open heart cardiothoracic procedures requiring cardiopulmonary bypass per year. Data from our centre show that many of our neonatal/paediatric patients require higher cardiac indexes than previously thought. We evaluated the new Pixie™ oxygenation system, rated from 0.1 L/min to 2 L/min, to determine if it could be used for these patients. Methods: Between 2010 and 2012, 250 Pixie™ oxygenators were used on consecutive patients requiring correction of congenital cardiac defects. Data were collected on Fi O2 requirements, oxygenator pressure drop and gaseous microemboli handling. Retrospective analysis was also undertaken on the procedures and demographics of all patients during 2011-2012 to determine the percentage of patients on whom the Pixie™ could be used. Results: Analysis of the procedures undertaken at Great Ormond Street Hospital (GOSH) showed that 89% were in patients under 20 kg, requiring a flow rate of <2 L/min (at a base cardiac index of 2.8 L/min/m 2 ). The maximum Fi O2 required at 2.5 L/min was 85%. Gaseous microemboli were reduced by 82.5±9.9% and bubble volume was decreased by 94.3±8.4% from the 'venous' pre-oxygenator to the 'arterial' post-oxygenator. Discussion: The Pixie™ oxygenator proved effective at flows up to 2.5 L/min, with air-handling capabilities comparable with other oxygenators. This represents a single oxygenator that could potentially be used to cover 89% of our surgical procedures. However, we believe that, for the smallest patients (i.e. < 2kg), a smaller priming oxygenator should be used in order to limit unnecessary haemodilution in this vulnerable group.